Deradicalization and strengthening of the state existence - Rosmawati, Rosmawati; Bakari, Yulianti; Harifuddin, Harifuddin (Technium Social Sciences Journal, 2022)
The purpose of this study is to reveal the strengthening of the government’s role in anticipating radicalism. For this reason, a study of literature related to radical movements and government efforts to anticipate them was conducted. Data sources of this research are articles or papers as secondary data. Therefore, data collection uses literature study techniques. Data analysis used Three-Track techniques, namely reduction, categorization, and drawing conclusions. The results obtained are (1) the role of the government or the state is to create a sense of security for its citizens, (2) strengthening the security sector in the form of main task and function’s improvements, and improving of security. (3) reorienting education towards multicultural education. (4) public-based social cultural campaign in the form of building public awareness to stop radicalism. Conclusion is the government needs to build public awareness through state defense and multiculturalism education in anticipation of radicalism.